1997
DOI: 10.1183/09031936.97.10102383
|View full text |Cite
|
Sign up to set email alerts
|

Pleurodesis in malignant pleural effusions: a randomized study of tetracycline versus bleomycin

Abstract: Malignant pleural effusions are commonly managed with tube thoracostomy drainage followed by chemical pleurodesis. Both tetracycline and bleomycin have been shown to be effective for intrapleural instillation, although neither agent has definitively proved advantages over the other. The aim of the present study was to compare these two agents in terms of response rate and toxicity profile.A prospective, randomized trial was carried out in a single centre. Between May 1993 and January 1996, 62 evaluable patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 14 publications
3
33
0
2
Order By: Relevance
“…Our study results conformed well to the previous result as clinical success occurred in 11 patients (73.3 3%) who received bleomycin, versus only 6 patients (40%) who took tetracycline. Moreover, treatment failure occurred more with the tetracycline group (9 patients, 60%); versus the bleomycin group (4 patients, 26.6%) [32,33] (see Fig. 1).…”
Section: Discussionmentioning
confidence: 90%
“…Our study results conformed well to the previous result as clinical success occurred in 11 patients (73.3 3%) who received bleomycin, versus only 6 patients (40%) who took tetracycline. Moreover, treatment failure occurred more with the tetracycline group (9 patients, 60%); versus the bleomycin group (4 patients, 26.6%) [32,33] (see Fig. 1).…”
Section: Discussionmentioning
confidence: 90%
“…Unlike doxycycline, bleomycin has been directly compared with tetracycline. Most of these studies demonstrated similar or higher success rates when utilizing bleomycin as a sclerosing agent, compared with tetracycline [117,128,129]. A direct study comparing doxycycline with bleomycin pleurodesis utilizing a small-bore catheter, demonstrated similar success rates (72% with bleomycin, 79% with doxycycline) [120].…”
Section: Chemical Pleurodesismentioning
confidence: 99%
“…As stated previously, direct studies comparing talc and bleomycin have demonstrated a superior pleurodesis success rate with talc [115,116,130]. An important criticism of bleomycin as a sclerosing agent involves its relative expense as compared with other sclerosing agents such as talc or doxycycline [129,131]. However, studies utilizing small-bore catheters and bleomycin have demonstrated successful pleurodesis [120,121] and therefore a potential overall cost saving when factors such as hospitalization, duration, and procedure costs are included.…”
Section: Chemical Pleurodesismentioning
confidence: 99%
“…3) [13][14][15][16][17][18][19][20][21], tetracycline (Fig. 4) [14,[22][23][24][25][26][27][28][29][30][31][32][33], bleomycin (Fig. 5) [34][35][36][37][38] and intrapleural chemotherapy and immunotherapy ( Fig.…”
Section: Which Is the Best Agent For Pleurodesis?mentioning
confidence: 99%